Exploration of Elementary School Teacher Education (PGSD) Students' Perceptions of the Teacher's Role in Developing Meaningful Learning Designs Based on Local Wisdom - Rachmadyanti, Putri; Rahman, Delfia Ikhlasiah; Yuliana, Ivo; Bahtiar, Reza Syehma; Hikmah, Sabila (CV Sinergi Ilmu dan Publikasi, 2025)
This research explores the perceptions of elementary school teacher education students regarding the role of teachers in developing meaningful learning based on local wisdom. It emphasizes the importance of preparing prospective teachers with contextual understanding and strong pedagogical skills. The study employed a descriptive qualitative approach, collecting primary data through semi-structured interviews with six participants selected purposively. Data analysis followed a deductive approach consisting of organizing and mapping data, breaking it down into meaningful parts, coding, interpreting patterns, and drawing conclusions. The ATLAS.ti 25 application was used to assist in mapping and organizing both primary and secondary data, including relevant lesson plans and literature. Results indicate that participants generally understand the concept of meaningful learning integrated with local wisdom, although their theoretical mastery is not yet comprehensive. They perceive the teacher's role as a facilitator, a learning designer, and a connector between students’ experiences and subject content through cultural context. Challenges identified include difficulties in recognizing relevant forms of local wisdom, limited access to supporting references, and the complexity of designing effective, thought-provoking questions for knowledge assimilation. The study concludes that meaningful learning based on local wisdom requires well-prepared prospective teachers with strong theoretical knowledge, practical pedagogical skills, and cultural awareness.